2020
DOI: 10.7880/abas.0200909a
|View full text |Cite
|
Sign up to set email alerts
|

Function of value stream mapping in operations management journals

Abstract: Studies of the value stream mapping (VSM) in Western journals report that leveraging VSM as a lean tool results in performance improvements. However, in these articles, VSM is functioning as a tool for partial optimization, attempting to identify and resolve bottlenecks in individual functions and divisions, primarily in production activities. For that reason, the greater the degree to which VSM underpins success, the more it deviates from the original essence of lean production and flow management, promoting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(27 citation statements)
references
References 85 publications
0
27
0
Order By: Relevance
“…It brings higher utilisation of capacity and higher flexibility in various functions of a SC. Furthermore, improving the time-based performance in the valueadding process or value chain (VC) brings incremental improvement in the lead time and develops sustainable competitive advantage (Tyagi et al, 2015;Rother and Shook, 2003;Fujimoto, 1999;Fujimoto, 2012;Hussain et al, 2011;Haefner et al, 2014;Fukuzawa, 2020). In the literature on lean manufacturing, authors had discussed various tools including Business Process Modelling Notation (BPMN), petri nets, value stream mapping (VSM), process mapping, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It brings higher utilisation of capacity and higher flexibility in various functions of a SC. Furthermore, improving the time-based performance in the valueadding process or value chain (VC) brings incremental improvement in the lead time and develops sustainable competitive advantage (Tyagi et al, 2015;Rother and Shook, 2003;Fujimoto, 1999;Fujimoto, 2012;Hussain et al, 2011;Haefner et al, 2014;Fukuzawa, 2020). In the literature on lean manufacturing, authors had discussed various tools including Business Process Modelling Notation (BPMN), petri nets, value stream mapping (VSM), process mapping, etc.…”
Section: Introductionmentioning
confidence: 99%
“…(Haefner et al. , 2014; Fukuzawa, 2020) to analyse and improve the time-based performance and other measures. In general, VSM has a wider acceptance in the research community.…”
Section: Introductionmentioning
confidence: 99%
“…1 This is just one example, and many manufacturing companies are proceeding with an approach to develop and utilize digital technology that can acquire and use real-time information related to "material and information flow" across the overall supply and value chain. For example, in the operations management field, one important lean tool that has been used to make the value stream in their own production system leaner is value stream mapping (VSM), in which a "material and information flow chart" is applied (Fukuzawa, 2020a;Rother & Shook, 1998). Fukuzawa (2020a) found that VSM was used as one of the important lean tools, and performance improvements were reported in extant literature of Western journals in the operations management field.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the operations management field, one important lean tool that has been used to make the value stream in their own production system leaner is value stream mapping (VSM), in which a "material and information flow chart" is applied (Fukuzawa, 2020a;Rother & Shook, 1998). Fukuzawa (2020a) found that VSM was used as one of the important lean tools, and performance improvements were reported in extant literature of Western journals in the operations management field. Fukuzawa (2020a) also found that VSM was used as a "partial optimization" tool to promote the discovery and improvement of bottlenecks in individual functions and divisions, mainly focusing on production activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation